Design and Synthesis of Butenolide‐based Novel Benzyl Pyrrolones: Their TNF‐α based Molecular Docking with In vivo and In vitro Anti‐inflammatory Activity. (1st March 2015) - Ali, Yakub; Alam, Mohammad Sarwar; Hamid, Hinna; Husain, Asif; Shafi, Syed; Dhulap, Abhijeet; Hussain, Firasat; Bano, Sameena; Kharbanda, Chetna; Nazreen, Syed; Haider, Saqlain
<x xml:space="preserve">Abstract</x> A focused library of novel benzyl pyrrolones has been synthesized and their in silico molecular docking studies carried out against TNF‐α target. Among all the docked molecules, compound 3f showed best glide score of −6.89. All the synthesized compounds were evaluated for in vivo anti‐inflammatory activity by carrageenan‐induced paw edema model. Compounds showing significant anti‐inflammatory activity were further tested for their in vitro TNF α expression. Compounds 3b and 2b were found to show significant inhibition of 76.22% and 71.47%, respectively after 5 h in comparison with standard drug indomethacin, which showed 80.98% inhibition of inflammation. Compounds 3b and 2b also suppressed TNF α level by 65.03% and 60.90% as compared indomethacin, which showed 68.84% of inhibition. Compound 3b showed significant analgesic activity of 60.04%, and its activity was comparable with indomethacin (64.04%). Compounds 3b and 2b were also tested for their effect on protein expression of COX‐2 and NF‐κB in the liver tissues. Compounds 3b and 2b were further evaluated for their gastric risk and lipid peroxidation action and showed superior GI safety along with reduction of LPO as compared to indomethacin. Hepatotoxicity study showed that these two compounds did not cause any damage to liver.